Keys to Understanding the Middle East - Payind, Alam; McClimans, Melinda (Open textbook library., 2017)
This book is intended for readers who have never studied the Middle East, or experts who may wish to fill gaps in their knowledge of the region from other disciplines. Whether for establishing or deepening one's knowledge of the region, these fundamentals are important to know. The languages, cultural, religious and sectarian communities of the region, and selected turning points and influential people in history are starting points for gaining an understanding of the diverse contexts of the region. It isbased on introductoryand graduatecourseson thecontemporaryMiddle East, which the Center's director, Dr. Alam Payind, has been teaching for the past 30 years. The book's co-author,Melinda McClimans,hastaught these and other courses with him, as well as her own,for the past 15years. The material isintendedengage with diverse – even conflicting – culturaland historicalperspectives,andways of perceivingboth Middle Easternandworld historyfrom perspectives within the region. It is not intended to reinforce a monolithic or matter-of-fact perception of the region.For this and many other reasons, images are an important aspect of the knowledge presented. Each chapter starts with links to its image galleries, along with other visual aids and key elements.